Health Prevention: An Overview of Hazardous Ingredients in Some Cosmetic Products Sold in Lomé (Togo) - Aboudoulatif, Diallo (European Journal of Applied Sciences, 2022)
Introduction: Several substances used in cosmetic products can be dangerous for human health. These substances can induce a public health problem, especially in developing countries such as Togo; where there is no strict control regarding cosmetic products. The objectives of this study were to verify the presence of hazardous ingredients on the labels of cosmetics products. Method: This study was a cross-sectional descriptive study, which focused on body and hygiene cosmetics, intended for children and adults, sold in pharmacies and in a market in Lomé. Results: In total, 800 cosmetics products were studied, including 400 in pharmacies and 400 in the market. At the pharmacy as in the market, 244 no-rinse cosmetics products (milks, creams, serums, oils and lotions) and 156 rinse-off cosmetics products (bar and gel soaps) were evaluated. Hazardous ingredients were present both on the labels of cosmetic products collected at the pharmacy as well as at the market. But some hazardous ingredients were more frequent on the labels of the market cosmetic than on those of the pharmacy. Substances banned by the European Union such as hydroquinone and clobestasol propionate; allergenic and prohibited perfumes such as hydroxyisohexyl-3-cyclohexene carboxaldehyde; regulated preservatives as methylparaben and banned ingredients such as methylisothiazolinone and isobutylparaben; and unclassified dangerous depigmenting substances such as kojic acid and glutathione were the main families of hazardous ingredients identified on the labels of cosmetic products. Conclusion: This study confirms the absence of a control and regulatory system concerning cosmetic products marketed in Lome (Togo).